Innovation in Ethno-STEM Teaching Materials: An Ethnoscience Study in Cengklungan Music - Eli Trisnowati; Wiyanto Wiyanto; Bambang Subali; Sulhadi Sulhadi; Tutik Arifah (International Conference on Science, Education, and Technology, 2022)
Local wisdom needs to be maintained, protected and preserved, so it does not become extinct. Therefore, scientific studies on extracting local wisdom from the community in schools are increasingly needed. There have been many previous ethnoscience studies, but there have yet to be any ethnoscience studies in the Temanggung district, Central Java, Indonesia. The purpose of this study was to identify and reconstruct the original science of the community contained in the presentation of the art of cengklungan music into scientific science in Ethno-STEM teaching materials. Data collection was carried out in Geblog Village, Kaloran District, Temanggung Regency, Indonesia. The research method used is descriptive qualitative with data collection techniques through observation and interviews. The obtained data is then analyzed, verified, reduced, and reconstructed into scientific science. The results showed that there were several studies of ethnoscience in the presentation of the art of cengklungan music on the material of vibration, waves, and sound. Three main elements in the presentation of the art of cengklungan music are vocals, instruments, and dance. The ethnoscience study is integrated into Ethno-STEM-based teaching material.